Дослідження шумів автогенераторів на лавино-пролітних діодах - Бурчін, Ю. О.; Жутова, М. М. (ХНУРЕ, 2025)
The work is devoted to both theoretical and practical research of fluctuation components of diode oscillators. The conducted researches testify to the correspondence of theoretical conclusions and practical results. The results of the work and the developed equipment can be used in further researches related to development of microwave diode oscillators.
Keywords: шум автогенератора; лавино-пролітний діод